“Our voice needs to be heard” : the impact of contract changes on clients of child and family services : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy at Massey University, Auckland, New Zealand - Gardiner, Blake (Massey University, 2023)
Caregivers of children balance unique complexities, dealing with their own personal commitments while often engaging with multiple agencies providing services to them and the children in their care. Child and family services that support caregivers and children are funded and contracted by the State through a process known as procurement where the State awards funding contracts to different community agencies. These funding contracts are susceptible to changes which can have profound impacts on caregivers’ lives. Contract changes occur when the State, holding decision-making power over the contract, makes contract alterations or funds another community agency for the contracted service. This qualitative-exploratory study aimed to explore how caregiver clients of State-funded community child and family services are impacted when contracts change resulting in a change of service for the client. This research found that clients’ needs were not accurately addressed or met within current procurement practice; communication and support for clients was lost during times of contract change; and there was a lack of available opportunity for clients to engage in a meaningful way with contract decision-making. These experiences resulted from mechanisms of neoliberalism, agency accountability to the State, and the current procurement approach which significantly impacted clients’ experiences. The findings highlighted that clients significantly impacted by contract changes are fully aware of this impact but felt their voices were ignored, keeping any contract decision-making out of their control. Further research exploring clients’ exclusion from decision-making and feedback provision would provide deeper insight into the systemic elements that inhibit clients sharing their voice when they have concerns about the support they receive. Finally, further research with a larger sample size would be of great benefit as this would provide a fuller picture of how contract changes impact on clients’ experiences of services.
Keywords: 440712 Social policy